Pengaruh Relationship Marketing Terhadap Loyalitas Konsumen Klinik Navaagreen Batam - Inda Sukati; Triana Ananda Rustam (Prosiding, 2023)
The concept of relationship marketing emerged in the fields of services marketing and industrial marketing. Relationship marketing combines offline and online strategies to strengthen bonds between businesses and customers. In essence, it involves investing heavily in connections with customer.. The objective of this study is to investigate how he trust, commitment, communication, and conflict handling influence the customer loyalty. The data collection instrument used was a questionnaire which was administrated to a total sample of 100 consumers of Navaagreen Batam Clinic. The analyses involved statistical methods such reliability and validity tests and multiple regression. The results indicated that there are positive significant relationship between (a) trust, (b) commitment, (c) communication and consumer loyalty at Navaagreen Batam Clinic. The finding also indicated that there is negative insignificant relationship between Handling Customer Complaints/Conflicts and consumer loyalty at Navaagreen Batam Clinic. The study therefore recommends that Navaagreen Batam Clinic need to implement the strategy to maintain customer trust, commitment and communication. The current study also suggest to Navaagreen Batam Clinic for improving the customer’s complaint handling system as well as to show more care and concern when relating to their customers as all these give the consumers a seen as assurance and honor as revealed by the study result.